GPS Monitoring: A Viable Alternative to the Incarceration of Nonviolent Criminals in the State of Ohio - Kucharson, Matthew K. (2006)
This article will discuss the emergence of GPS technology in the field of criminal law and propose that Ohio embrace GPS monitoring as an alternative to the incarceration of nonviolent offenders. Part II will begin by briefly outlining the history of GPS technology. Part II will then discuss the use of GPS monitoring in the field of law enforcement. Specifically, this Part will illustrate the different components necessary for the implementation of an effective GPS monitoring program and explain the use of inclusion and exclusion zones. Part III will examine the status of Ohio's state prison system and will focus on the historical costs associated with housing prisoners Part III will also briefly discuss recent changes to Ohio's criminal sentencing laws that positively impact and encourage the use of new offender monitoring technology, such as GPS. Part IV will reveal how a properly executed GPS monitoring program can be a constitutional, cost-effective, and community-friendly alternative to the incarceration of nonviolent criminals. Part V will conclude by recommending that Ohio implement a GPS offender monitoring program to be used as an alternative to the incarceration of nonviolent offenders within the state